Cybercrime and subculture of cybercriminals - Kotukh, Yevgen V.; Kislov, Denis V.; Yarovoi, Tykhon S.; Kotsiuba, Ruslana O.; Bondarenko, Oleksandr H. (Linguistics and Culture Review, 2021)
Unlike traditional types of crime, such as murder or theft, that have a long history, cybercrime is a relatively young phenomenon and a new one that emerged with the advent of the Internet. It should be noted that the very nature of the Internet is quite favourable for committing crimes. Its properties such as globality, cross-border nature, the anonymity of users, wide audience coverage, distribution of main network nodes, and their interchangeability create advantages for cybercriminals who use the Internet at all stages of crime and also allow them to effectively hide from law enforcement agencies. An important aspect of cybercrime that contributes to its spread and hinders the fight against it is the subculture of cybercriminals. This subculture needs to be given special attention, so this issue is discussed in detail in the article. Therefore, the purpose of the article was to analyse cybercrime as one of the youngest types of crime in the modern world. The history of the emergence of cybercrime and cyber-security was considered, the types of cybercrime were characterized, and the functions of cybercrime were analysed.